2013
DOI: 10.1002/qre.1614
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Process Yield for Circular Profiles

Abstract: Two indices C p (circular) and C pk (circular) based on the functional method have been proposed to measure the process capability of circular profiles. However, these two indices only provide potential capability and a lower bound on the process yield, respectively. In this paper, we develop a new yield index S pk (circular) for circular profiles. This index provides an exact measure of process yield. The asymptotic normal distribution of the estimated index is derived. The statistical inferences such as hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The accuracy of the natural estimator has been investigated with a simulation technique [28]. The process yields for some specified cases, such as the imprecise sample data, circular profiles, autocorrelation between linear profiles, and multiple stream processes, have been analyzed in some literature [29][30][31][32]. In the above researches, the index was used to only reflect the process capability.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the natural estimator has been investigated with a simulation technique [28]. The process yields for some specified cases, such as the imprecise sample data, circular profiles, autocorrelation between linear profiles, and multiple stream processes, have been analyzed in some literature [29][30][31][32]. In the above researches, the index was used to only reflect the process capability.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results showed that the simultaneous application of these three methods could provide comprehensive information about the process capability of multivariate linear profiles. Wang proposed a method for precise measurement of PCI of circular profiles. Wang also proposed a method for measuring the exact value of PCI for simple linear profiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, those indices only provide an approximate measure rather than an exact measure of the process yield. A process yield index S pkA for simple linear, nonlinear, and circular profiles have been proposed to evaluate the process yield …”
Section: Introductionmentioning
confidence: 99%
“…A process yield index S pkA for simple linear, nonlinear, and circular profiles have been proposed to evaluate the process yield. [13][14][15][16] Comparing the process yield for linear profiles is an essential task in managing supply chains. Two methods such as the difference test statistic and the ratio test statistic can be used to solve this comparison problem.…”
Section: Introductionmentioning
confidence: 99%